Constitutional changes and improvement of the organisation and functioning of public authority in the regions of the Russian Federation - Andrichenko, Lyudmila V.; Maslovskaya, Tatiana S.; Plyugina, Inna V. (Journal of the Belarusian State University. Law, 2021)
Constitutional modernisation in the Russian Federation involves a large-scale revision and updating of legislation regulating the organisation and functioning of public authority. Many institutions have undergone transformation, new legal acts have been adopted, including federal constitutional laws, and measures are being worked out to improve the coordination and interaction of public authorities. Despite the fact that the relevant changes primarily concerned the federal state authorities, they could not affect the existing organisation and functioning of public authorities at the regional level. The article analyses these issues in the context of constitutional developments: it gives a legal assessment of the liquidation of the constitutional (statutory) courts of the subjects of the Russian Federation; it draws attention to the difficulties of coordination and interaction of public authorities at the regional level. The article highlights the legal consequences of attributing to the subjects of the Russian Federation the issue of establishing restrictions for the replacement of state and municipal positions, positions of state and municipal service.
Keywords: public authorities; state authorities of the subjects of the Russian Federation; local authorities; the Constitution of the Russian Federation; constitutional developments; constitutional (statutory) courts of the subjects of the Russian Federation; state and municipal offices